Zygophyllum album aqueous extract reduces oxidative damage in red blood cells and attenuates pro-inflammatory plasma markers in hypercholesterolemic-diabetic rats - Yasmina BAHLIL; Djamil KROUF; Nawal TALEB-DIDA (International Journal of Phytomedicine, 2020)
Zygophyllum album (Z. album) is used in traditional medicine for a long time for its anti-diabetic activities. This study had to assess Z. album extract supplementation effects on redox and inflammatory statuses in hypercholesterolemic-diabetic rats. Male rats Wistar (n=36), weighing 200±10 g were divided into three groups (n=12). The first group was rendered hypercholesterolemic (HC) with a high cholesterol diet (1 %). The second group was rendered diabetic (D) by intraperitoneal injection of streptozotocin (STZ) (35 mg/kg of body weight). The third group was rendered hypercholesterolemic-diabetic (HC-D); each group was divided into two groups (n=6), untreated groups (HC, D, HC-D) and treated groups with 1 % Z. album extract (HC-Za, D-Za and HC-D-Za). After 28 days, Z. album treatment lead to a decrease in RBC’s TBARS contents in HC-Za (-44 %), D-Za (-66 %) and HC-D-Za (-23 %) groups. An increase in the antioxidant enzymes activities (superoxide dismutase, glutathione peroxidase, glutathione reductase and catalase) was observed in HC-Za, D-Za and HC-D-Za (p <0.05). IL-1 β and IL-6 concentrations were reduced by -44, -50 and -33 % and -49, 38 and -41 %, respectively in treated groups. A decrease in TNF-α as well as homocysteine and CRP was observed in Z. album treated groups (p <0,05). In conclusion, Z. album reduces radical attack and improves the anti-inflammatory proprieties in hypercholesterolemic-diabetic rats.